A lightweight scalable agarose-gel-synthesized thermoelectric composite. (16th March 2018) - Kim, Jin Ho; Fernandes, Gustavo E; Lee, Do-Joong; Hirst, Elizabeth S; Osgood, Richard M; Xu, Jimmy
Abstract: Electronic devices are now advancing beyond classical, rigid systems and moving into lighweight flexible regimes, enabling new applications such as body-wearables and 'e-textiles'. To support this new electronic platform, composite materials that are highly conductive yet scalable, flexible, and wearable are needed. Materials with high electrical conductivity often have poor thermoelectric properties because their thermal transport is made greater by the same factors as their electronic conductivity. We demonstrate, in proof-of-principle experiments, that a novel binary composite can disrupt thermal (phononic) transport, while maintaining high electrical conductivity, thus yielding promising thermoelectric properties. Highly conductive Multi-Wall Carbon Nanotube (MWCNT) composites are combined with a low-band gap semiconductor, PbS. The work functions of the two materials are closely matched, minimizing the electrical contact resistance within the composite. Disparities in the speed of sound in MWCNTs and PbS help to inhibit phonon propagation, and boundary layer scattering at interfaces between these two materials lead to large Seebeck coefficient (> 150 μ V/K) (Mott N F and Davis E A 1971 Electronic Processes in Non-crystalline Materials (Oxford: Clarendon), p 47) and a power factor as high as 10 μ W/(K 2 m). The overall fabrication process is not only scalable but also conformal and compatible with large-area flexible hosts including metal sheets, films, coatings, possibly arrays of fibers, textiles and fabrics. We explain the behavior of this novel thermoelectric material platform in terms of differing length scales for electrical conductivity and phononic heat transfer, and explore new material configurations for potentially lightweight and flexible thermoelectric devices that could be networked in a textile.